2015
DOI: 10.1111/eos.12238
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the effects of hydraulic calcium silicate dental cements on plasma and liver aluminium levels in rats

Abstract: Our aim was to test whether the presence of three hydraulic calcium silicate dental cements--MTA Angelus, MTA Fillapex, and Theracal LC--in the dental extraction socket of an in vivo model, would affect the levels of aluminium (Al) in the plasma and liver. Following anesthesia, the right upper incisor of each male Wistar albino rat was extracted and polyethylene tubes filled with MTA Angelus, MTA Fillapex, or Theracal LC were inserted into the depth of the extraction socket and gingival tissue was sutured. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 55 publications
6
44
0
3
Order By: Relevance
“…Therefore, diabetes mellitus is a chronic metabolic inflammatory disease associated with altered calcium homoeostasis and bone marker expression (Levy et al 1994). While the systemic effects of MTA treatment are already documented (Khalil & Eid 2013, Demirkaya et al 2016, Simsek et al 2016, no study has addressed its systemic effects on the expression of bone markers under diabetic conditions. While the systemic effects of MTA treatment are already documented (Khalil & Eid 2013, Demirkaya et al 2016, Simsek et al 2016, no study has addressed its systemic effects on the expression of bone markers under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, diabetes mellitus is a chronic metabolic inflammatory disease associated with altered calcium homoeostasis and bone marker expression (Levy et al 1994). While the systemic effects of MTA treatment are already documented (Khalil & Eid 2013, Demirkaya et al 2016, Simsek et al 2016, no study has addressed its systemic effects on the expression of bone markers under diabetic conditions. While the systemic effects of MTA treatment are already documented (Khalil & Eid 2013, Demirkaya et al 2016, Simsek et al 2016, no study has addressed its systemic effects on the expression of bone markers under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MTA to release Ca +2 upon hydration has been reported previously (De Vasconcelos et al 2009). Demirkaya et al (2016) reported that the substances released by MTA in surrounding tissues can enter the bloodstream and can be transported to distant sites upon tissue damage. These findings are in agreement with previous investigations that measured the release of Ca 2+ from polyethylene tubes filled with the same MTA materials and immersed in deionized water.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate went up to 100% with a pre-treatment of laser irradiation to the exposed pulp 14) . Calcium silicates/MTA-based materials and Portland cements contain trace amount of heavy metals, such as lead (Pb), arsenic (As), cadmium (Cd), nickel (Ni), iron (Fe), copper (Cu), manganese (Mn), and zinc (Zn) 39) . It was reported that the MTA/Portland cements materials, such as CPM (Egeo, Buenos Aires, Argentina), CPM Sealer (Egeo), Gray MTA-Angelus (Angelus), ProRoot-MTA (Dentsply Tulsa Dental), and Gray Portland cement (Votorantim Cimentos, Cubatão, SP, Brazil) contained arsenic levels higher than the ISO-recommended limit for water-based cements of 2 mg arsenic/kg material (ISO 9917-1 standard).…”
Section: Calcium Silicates and Resin-modified Calcium Silicatesmentioning
confidence: 99%
“…An in vivo study using rats compared the release of heavy metal (aluminium) from three different type of calcium silicate-based materials: MTA Angelus, MTA Fillapex (containing MTA, salicylate resin, natural resin, bismuth oxide, and silica), and resin-containing TheraCal LC. After 6, 30, and 60 days of restorations with these materials, the levels of aluminium (Al) in the plasma in which MTA Angelus (322-529 ppb) and MTA Fillapex (299-468 ppb) were implanted, were around twice as high as Theracal LC (143-226 ppb) and the control (102-155 ppb) groups 39) . It is likely that TheraCal LC released less Al because of its lower solubility 31) and shorter setting time (immediately lightcured) which reduces the chance of Al-release prior to the setting of the material 39) .…”
Section: Calcium Silicates and Resin-modified Calcium Silicatesmentioning
confidence: 99%
“…In addition, trivalent inorganic ions, like Al 3+ , increase Fgf-2 expression, which plays a relevant role in osteogenesis and cementogenesis (13). However, Demirkaya et al (14) reported increase of Al levels in plasma and liver after treatment with hydraulic calcium silicate cements. Furthermore, calcium aluminate is able to promote strong increase in the mechanical strength of the biomaterial, which is an indispensable requisite for scaffolds (15).…”
Section: Introductionmentioning
confidence: 99%